Follow-up study of dental students’ esthetic perceptions of mild dental fluorosis - Levy SM, Warren JJ, Jakobsen JR. (Blackwell Synergy, 2002)
Several studies have assessed people’s esthetic perceptions of dental fluorosis, suggesting that concerns may be greater than believed previously. Few studies have assessed dental students’ perceptions and none has done so over time.